Bta-miR-10b Secreted by Bovine Embryos Negatively Impacts Preimplantation Embryo Quality - Lin, Xiaoyuan; Pavani, Krishna Chaitanya; Smits, Katrien; Deforce, Dieter; Heindryckx, Björn; Van Soom, Ann; Peelman, Luc (Frontiers in Genetics, 2019)
In a previous study we found miR-10b to be more abundant in conditioned culture medium of degenerate embryos compared to that of blastocysts. Here we show that miR-10b mimics added to the culture medium can be taken up by embryos. This uptake results in an increase in embryonic cell apoptosis and aberrant expression of DNA methyltransferases (DNMTs). Using several algorithms Homeobox A1 (HOXA1) was identified as one of the potential miR-10b target genes and dual-luciferase assay confirmed HOXA1 as a direct target of miR-10b. Microinjection of si-HOXA1 into embryos also resulted in an increase in embryonic cell apoptosis and downregulation of DNMTs. Cell progression analysis using Madin-Darby bovine kidney cells (MDBKs) showed that miR-10b overexpression and HOXA1 knockdown results in suppressed cell cycle progression and decreased cell viability . Overall, this work demonstrates that miR-10b negatively influences embryo quality and might do this through targeting HOXA1 and/or influencing DNA methylation.